Characteristics between pulsating aurora, energetic electron precipitation and chorus emissions observed at Syowa Station: A case study on 17 May 2007 - Hiroyasu, Tadokokoro; Mitsunori, Ozaki; Yuto, Katoh; Yoshizumi, Miyoshi; Hisao, Yamagishi; Akira, Kadokura; Yoshimasa, Tanaka (2013)
第4回極域科学シンポジウム 個別セッション：[OS] 宙空圏 11月14日（木）〜15日（金）国立極地研究所 2階大会議室前ラウンジ conference object